Assessment of potential winter hardiness in winter bread wheat cultivars and genotypes by analyzing autofluorescence in seedling tissues - I. V. Karkhardin; A. A. Konovalov; N. P. Goncharov (Труды по прикладной ботанике, генетике и селекции)
Background. Winter crops are the most productive component of agricultural biocenoses. In Russia, winter wheat suffers the greatest losses in winter, so a search for traits marking high or low winter hardiness in autumn-sown genotypes, including improved cultivars, is needed to assess their potential for overwintering. One of such markers of high winter hardiness is an increased lignin content in plant tissues. The terminal enzyme in the phenylpropanoid pathway of metabolism, wherein lignin components are formed, is cinnamyl-alcohol dehydrogenase (CAD, EC 1.1.1.195). In plants, the CAD enzyme is one of the links in the aromatic metabolism, which generates, in addition to lignin, a number of aromatic compounds, such as lignans, aromatic glycosides, etc. Many of these compounds, like lignin, contain chromophore groups and are capable of autofluorescence. Correlations of the genotypes that incorporate CAD1-F with overwintering are studied in this work.Materials and methods. The winter bread wheat cultivars ‘Zitnica’ (Yugoslavia) and ‘Novosibirskaya 9’ (ICG SB RAS, Russia), contrasting in winter hardiness and CAD isozyme spectra, their hybrids, and 28 improved winter cultivars developed in Krasnodar were selected for the study. Fluorescence analysis of 28 winter wheat cultivars was also performed. Correlation coefficients between fluorescence and frost tolerance were calculated using the results of the analysis of 7 most contrasting cultivars.Conclusions. The tested winter bread wheat genotypes demonstrated the interplay between CAD1-F and successful overwintering: a correlation was found in the genotypes carrying the 00 CAD1-F allele with higher percentage of overwintered plants. This dependence was not observed in every season. The analysis of seedling sections for fluorescence can also be used for preliminary assessment of winter tolerance in winter bread wheat under laboratory conditions.